UPAYA ORANG TUA DALAM MENINGKATKAN MOTIVASI ANAK BELAJAR BACA AL-QUR’AN DI TPQ MUAMALAH DESA PEDADA KECAMATAN TELUK KERAMAT - Dary Patriawan (EDUCATIONAL JOURNAL : General and Specific Research, 2022)
This study aims to obtain clear information about: a) The views of parents in Pedada Village on the existence of TPQ Muamalah Pedada Village; b) A description of the motivation of parents in getting their children to learn to read Al-Qur'an at TPQ Muamalah, Pedada Village; c) The role of parents in motivating their children to study at TPQ Muamalah, Pedada Village. The subjects of this study were the Head of the TPQ and the parents of the children in TPQ Muamalah, Pedada Village. To obtain data related to the research focus, the researcher conducted interviews, observations and documentation. The data analysis technique used is qualitative data analysis. In this study, researchers used three techniques, namely: 1) observation extension technique; 2) triangulation technique; 3) member check technique. The research results can be concluded: 1) Parents' views on the importance of the TPQ Muamalah Desa Pedada at this time are as follows: (a) Can provide examples; (b) To motivate children to learn; (c) Creating a religious child. 2) Parents' motivation in getting their children to learn to read Al-Qur'an at TPQ Muamalah Pedada Village is as follows: (a) Can reduce children's play time; (b) Children are not bored and bored when learning to read the Al-Qur'an; (c) Motivation to learn to read Al-Qur'an for children is increasing. 3) The role of parents in increasing motivation to learn to read Al-Qur'an at TPQ Muamalah Pedada Village is as follows: (a) Teaching discipline to children; (b) Teach good akhalak; (c) Make children pious and sholeha.